PELAKSANAAN TUGAS ROOM ATTENDANT DI DEPARTEMEN HOUSEKEEPING LABERSA TOBA HOTEL AND CONVENTION CENTRE BALIGE - Yuni Angelina; Siti Sofro Sidiq (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
A hotel is a sort of professionally managed accommodation that offers guests sleeping quarters, food & drink, and other amenities. The Housekeeping Department is one of the most important parts of any hotel. It is the job of the hotel's Housekeeping Department to ensure that all guest rooms, common spaces, restaurants, bars, and other service areas are clean, orderly, and comfortable. Room attendants and other members of the Housekeeping Department's support staff help ensure that visitors staying in and visiting the hotel have a pleasant experience by maintaining clean, organized, and well stocked guest rooms. The Labersa Toba Hotel and Convention Center Balige, which is one of the 4-star standard hotels in Toba, offers some of the greatest service, notably in the Housekeeping Department, in order to boost client satisfaction. The research was conducted at the Labersa Toba Balige Hotel to better understand the procedures of the room attendant Housekeeping department and the challenges that were encountered during their implementation. This study makes use of qualitative data analysis approaches, such as analysis, description, and summarization of circumstances and scenarios gleaned through interviews and field observations of the topics under investigation. Keywords : hotel, housekeeping department, room attendant.